A novel method of producing lightweight microcellular injection molded parts with improved ductility and toughness. (15th January 2015) - Sun, Xiaofei; Kharbas, Hrishikesh; Peng, Jun; Turng, Lih-Sheng
Abstract: This paper presents a novel method and the underlying mechanisms of improving the ductility and toughness of polymer blend components using microcellular injection molding. By producing a special microcellular structure and morphology in polymer blends of proper material formulations, the ductility and toughness of the foamed parts can be significantly improved compared to those of solid parts. The key is to achieve a microcellular structure with a sub-micron scale immiscible secondary phase uniformly dispersed in the primary polymer matrix. Upon tensile loading, cavitation of the secondary phase facilitates the interconnection of microcellular voids to form channels such that the stretched component transforms into a bundle of fibrils. This change in structure turns the fracture mechanism from crack propagation across the matrix into shear yielding of a bundle of fibrils in the loading direction. Process conditions, microstructures, phase morphologies, and mechanical test results of three different types of polymer blends, namely, polypropylene/high-density polyethylene (PP/HDPE), polypropylene/low-density polyethylene (PP/LDPE), and poly(lactic acid)/poly(3-hydroxybutyrate-co-3-hydroxy-valerate) (PLA/PHBV) blends, are presented. Compared with other toughening methods, this method achieved a more significant improvement in ductility and toughness while reducing material consumption and part weight. Graphical abstract: Highlights: A novel method which leads to significant improvement in ductility has been proposed. The mechanism of this ductility enhancing has been investigated and reported herein. The key to ductility enhancement is to achieve a microcellular structure with a sub-micron scale immiscible secondary phase. This method has been successfully applied on PP/HDPE, PP/LDPE, and PLA/PHBV blends.